2015
DOI: 10.1007/s10157-015-1147-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of modest exercise in Japanese patients with chronic kidney disease: a single-armed interventional study

Abstract: Our modest exercise program improved the physical performance of CKD patients without deterioration of renal function. These results suggest that exercise rather than excess rest should be recommended for CKD patients to avoid muscle wasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 36 publications
1
43
0
1
Order By: Relevance
“…In the study supported by (Hamada, et al, 2016) who reported that modest physical exercise program will upgrade the physical functional status of CKD patients undergoing HD treatment and will not a reason for any functional deterioration of the renal functional tests, in addition the same authors reported that, the exercise program should be included in the routine care of stage 4, or 5 CKD patients [27]. Also (Stewart, 2017) supported that, the intradialytic exercise program may raise the efficiency of the dialysis treatment by improving the efflux of urea from the tissue to the vascular closet resulting in an increase in serum urea clearance [28].…”
Section: Discussionmentioning
confidence: 95%
“…In the study supported by (Hamada, et al, 2016) who reported that modest physical exercise program will upgrade the physical functional status of CKD patients undergoing HD treatment and will not a reason for any functional deterioration of the renal functional tests, in addition the same authors reported that, the exercise program should be included in the routine care of stage 4, or 5 CKD patients [27]. Also (Stewart, 2017) supported that, the intradialytic exercise program may raise the efficiency of the dialysis treatment by improving the efflux of urea from the tissue to the vascular closet resulting in an increase in serum urea clearance [28].…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, another study of 16 older adults with Stage 4 CKD demonstrated that 12 weeks of physical activity also improved performance on the ‘Get Up and Go’ test [ 13 ]. Six months of physical activity improved performance on the 30 second ‘Sit-to-Stand’ test in 47 persons with CKD [ 14 ]. Four studies demonstrated that a physical activity intervention of 12 or more weeks improved performance on the six meter walk test in CKD patients [ 12 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary change can influence on the amount of proteinuria (20,21). Excessive exercise can increase proteinuria temporarily (22), while modest exercise has a preferable effect on proteinuria in patients with stable CKD (23).…”
Section: Discussionmentioning
confidence: 99%